Unilateral Renal Agenesis: Prenatal Diagnosis and Postnatal Issues - Waldo Sepulveda; Amy E. Wong; Gabriele Tonni; Gianpaolo Grisolia; Angela C. Ranzini (Diagnostics)
Unilateral renal agenesis (URA) is a urinary tract congenital anomaly characterized by a congenital absence or early developmental arrest of only one kidney. In the presence of a normal contralateral kidney, URA is typically considered a condition of minimal clinical significance as the solitary kidney often undergoes hypertrophy and can sufficiently perform the needed renal function after birth. However, postnatal studies suggest that URA has a significant association with other urinary and extra-urinary anomalies and may have implications for long-term health. This descriptive review focuses on the perinatal aspects of URA, emphasizing the main ultrasound findings to establish the prenatal diagnosis and to guide perinatal management. The pediatric implications of this diagnosis, particularly the high prevalence of long-term complications including hypertension, proteinuria, and a decreased glomerular filtration rate, are also briefly reviewed. URA is consistently associated with other ipsilateral urogenital anomalies. In females, there is a significant association with uterine anomalies that has significant implications for subsequent reproductive function. In males, the prevalence of both urinary and genital anomalies is also increased, which may also have implications for future fertility. Prenatal ultrasound offers the possibility of early diagnosis and parental counseling, which may result in timely intervention to reduce contralateral renal damage, prevent severe urogenital manifestations and co-morbidities, and improve fertility and the quality of life.